2017
DOI: 10.1186/s12913-017-2246-8
|View full text |Cite
|
Sign up to set email alerts
|

“It’s so hard taking pills when you don’t know what they’re for”: a qualitative study of patients’ medicine taking behaviours and conceptualisation of medicines in the context of rheumatoid arthritis

Abstract: BackgroundPatients with chronic illnesses are often required to take lifelong medication to alleviate symptoms and prevent disease progression. Many patients find it difficult to adhere to prescribed medication for various reasons, some of which may link to the way they conceptualise medicines and understand their illness and treatment. This study explores the medicine taking behaviours of patients presenting with Rheumatoid Arthritis (RA), a chronic inflammatory autoimmune disease. We focused particularly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
0
12
0
4
Order By: Relevance
“…Patients tend to have a positive perception of MTX with some concerns . The development of adverse events and the fear of developing adverse events might affect adherence and willingness to continue therapy …”
Section: Discussionmentioning
confidence: 99%
“…Patients tend to have a positive perception of MTX with some concerns . The development of adverse events and the fear of developing adverse events might affect adherence and willingness to continue therapy …”
Section: Discussionmentioning
confidence: 99%
“…Patients are increasingly being asked to manage many aspects of their care, including communicating health information between healthcare providers and maintaining records of their own health [6,7]. Numerous studies have indicated that patients are sometimes unaware or incorrect about why they are taking a particular medication [8,9]. Adding RFU to medication labels would allow patients to always have RFU along with their medications and could improve adherence to prescribed medication treatments [6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, social anthropological literature conceives the term therapeutic itinerary as individuals or groups' actions towards health recovery, which may mobilize different resources, including homemade remedies (Cabral et al, 2011). The literature already addresses the theme of selfadjustment of drug therapy by patients (Waheedi et al, 2017;Kobue, Moch, Watermeyer, 2017, Laue, Melbye, Risør, 2017. However, few discussions address how this phenomenon occurs from caregivers perspective, which reinforces the importance of this study results.…”
Section: Drug Therapy Administrationmentioning
confidence: 54%